Evaluating the use of personal connections to bypass formal procedures: A study of vriski in Republic of Macedonia - Colin C. Williams; Slavko Bezeredi (UTMS Journal of Economics, 2017)
The soliciting of personal favours for and from others in order to circumvent formal procedures is a common practice across the world, variously known as guanxi, wasta, blat, and jeitinho. Until now, however, there have been no known empirical studies of this practice in South-East Europe. This paper fills that gap. The aim is to evaluate the extent to which personal connections are used to circumvent formal procedures, and who engages in such practices in FYR Macedonia. Reporting data collected from 2,014 face-to-face interviews undertaken in late 2015, the finding is that 35 per cent of respondents had used vrski during the year prior to the survey, particularly to gain access to health services and find a job. Using logistic regression analysis, the population groups significantly more likely to have used vrski are found to be younger people, higher income groups, those who also both supply and purchase undeclared work, live in rural areas or villages, while those in the Eastern, Southeastern and Pelagoni regions are less likely to do so than those in the Vardar region. The paper concludes by discussing the theoretical and policy implications along with the future research required.
Keywords: J46; K42; O17; P37; 330; informal economy; corruption; cronyism; nepotism; South-East Europe